Dianion and Dication of Tetracyclopentatetraphenylene as Decoupled Annulene‐within‐an‐Annulene Models. Issue 6 (23rd December 2021) - Miyoshi, Hirokazu; Sugiura, Ryosuke; Kishi, Ryohei; Spisak, Sarah N.; Wei, Zheng; Muranaka, Atsuya; Uchiyama, Masanobu; Kobayashi, Nagao; Chatterjee, Shreyam; Ie, Yutaka; Hisaki, Ichiro; Petrukhina, Marina A.; et al.
Abstract: The dianion and dication of tetramesityl‐substituted tetracyclopentatetraphenylene, a circulene consisting of alternating five‐ and six‐membered rings, have been generated by reduction with alkali metals and oxidation with antimony(V) halides, respectively. They are theoretically predicted to adopt double annulenoid structures called annulene‐within‐an‐annulene models in which the outer and inner conjugation circuits are significantly decoupled. The theoretical structures were experimentally proven by X‐ray crystallographic analyses and the electronic configurations were supported by MCD spectra. Based on the 13 C NMR chemical shifts, negative and positive charges are shown to be located mainly at the outer periphery, indicating that the dianion and dication have delocalized 22‐π and 18‐π electron outer perimeters, respectively, and 8‐π electron structure at the inner ring. Notably, the dianion has an open‐shell character, whereas the dication has a closed‐shell ground state. Abstract : Dianion and dication of a tetracyclopentatetraphenylene derivative were generated and investigated as the annulene‐within‐an‐annulene models. Experiments based on X‐ray crystallography and 1 H NMR, 13 C NMR, and MCD spectroscopies indicate that the outer and inner conjugation circuits are significantly decoupled, strongly supporting the theoretically predicted structures.